Assembly of Helicene‐Capped N, P, N, P, N‐Helicands within CuI Helicates: Impacting Chiroptical Properties by Ligand–Ligand Charge Transfer1. Issue 7 (10th January 2013) - Vreshch, Volodimir; El Sayed Moussa, Mehdi; Nohra, Brigitte; Srebro, Monika; Vanthuyne, Nicolas; Roussel, Christian; Autschbach, Jochen; Crassous, Jeanne; Lescop, Christophe; Réau, Régis
<x xml:space="preserve">Abstract</x> Combining helicate and helicene chemistry: Pentadentate phosphole‐pyridine helicands (see scheme) coordinated to CuI or AgI centers afford configurationally stable double‐stranded helicates bearing multiple bridging‐phosphane coordination modes. Similarly enantiomerically pure helicene‐grafted helicands afford enantiopure helicates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>